Integritas Diri bagi Kesehatan Mental (Depresi, Ansietas dan Stress) pada Lansia - Imelisa, Rahmi; Safarina, Lina; Suharjiman, Suharjiman (Journal of Telenursing (JOTING), 2024)
This study aims to analyze the relationship between the achievement of self-integrity in the elderly and the mental health of the elderly. The method used is a correlation study with a cross-sectional approach. The results showed that 81.8% of the elderly had good self-integrity. 9.1% of the elderly experienced mild depression, 12.1% experienced mild anxiety, and none experienced stress (0%). The results of the bivariate analysis showed that there was no significant relationship between self-integrity and depression (p-value = 0.547), and there was no significant relationship between self-integrity and anxiety (p-value = 0.441). In conclusion, there is no relationship between self-integrity and mental health in the elderly. Keywords: Anxiety, Depression, Self-Integrity, Elderly, Stress